'Time to construct positive identities': display questions in post observation teacher feedback. Issue 3 (2nd July 2020) - Donaghue, Helen
ABSTRACT: This article focuses on the use of display questions to construct positive identities in post observation feedback talk between in-service English language teachers and a supervisor. Using a linguistic ethnographic framework, microanalysis of dyadic feedback interaction is supplemented with ethnographic data gathered from participant perspective interviews and researcher knowledge of the research site and participants. Results show that display questions give feedback participants the opportunity to voice their knowledge and expertise thereby enabling them to claim positive identities. Display questions are also used by the supervisor to claim a practising teacher identity in order to reassure teachers of his worth as an observer and leader. Display questions help the supervisor perform a manager identity as they allow him to control the topic and evaluate teachers. While some teachers verify this identity by complying and providing the required answer, one teacher resists, replying reluctantly and with irritation, thereby contesting the supervisor's manager identity. This shows that identities are fluid, contestable, and discursively accomplished in situated feedback talk. Two practical implications are discussed: (1) the need for further research into feedback with in-service teachers (2) the suggestion that supervisors examine extracts from feedback to help them become more reflective and critical practitioners.